West Nile virus: measures against emergence - Mohamed Mustapha, Noordin; Abd Rahman, Yasmin (MedWin Publishers, 2019)
West Nile virus has a potential to emerge in new areas and cause large epidemics as was witnessed in the United States following its introduction in 1999. The virus is now a global public health threat, having been detected on every continent except Antarctica. Once restricted to Africa, its expansion beyond its natural habitat is related to some viral, vectoral, anthropologic and environmental factors. The successful establishment and spread of the virus depend in part on viral adaptations, availability of competent hosts and mosquito vectors and suitable environmental conditions. A combination of measures can be applied to minimise the likelihood of a WN virus epidemic. Available vaccines are only for veterinary use, human vaccines are still in development. Vector control, animal vaccination, targeted surveillance and strong cooperation between relevant authorities are important in preventing aWN virus epidemic in Malaysia.